Study on the correlation between energy availability and subclinical menstrual disorders - Bingzheng, Zhou; Zhuo, Jin; Qihao, Wang; Lunhao, Bai (Frontiers in Nutrition, 2024)
Background: There are few studies on the correlation between energy availability (EA) and subclinical menstrual disorders (SMD) in female athletes. This study aims to explore the differences in EA between female athletes with eumenorrhea and those with SMD, and the correlation between EA and the occurrence of SMD.Methods: Luteal phase defect (LPD) and anovulation were defined as SMD. Fifty-six adult female college athletes with regular menstrual cycles and no clinical symptoms of menstrual disorders (MD) were selected as subjects. The EA of the subjects was monitored, and SMD were identified. The EA was compared between the two groups, and the correlation between EA and the occurrence of SMD was analyzed.Results: Nineteen subjects were identified as LPD, and 7 subjects were identified as anovulation. The occurrence of SMD was 46.4%. The EA of subjects with SMD was lower than that of subjects with eumenorrhea (t = 3.165, p = 0.003), and EA was negatively correlated with the occurrence of SMD (r = -0.396, p = 0.000).Conclusions: There were differences in EA between female college athletes with eumenorrhea and SMD. EA was negatively correlated with the occurrence of SMD.